1996
DOI: 10.1046/j.1365-2443.1996.d01-224.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of XRad51.1 protein, Xenopus RAD51 homologue: recombinant XRad51.1 promotes strand exchange reaction

Abstract: Background: The RAD51 gene of Saccharomyces cerevisiae is homologous to the Escherichia coli recA gene and plays a key role in genetic recombination and DNA double-strand break repair. To construct an improved experimental system of homologous recombination in higher eukaryotes, we have chosen the South African clawed frog, Xenopus laevis, whose egg extracts might be useful for the in vitro studies. We identified and characterized a Xenopus homologue of RAD51 gene, the XRAD51.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
2
32
1
1
Order By: Relevance
“…In previous studies, observations on the interaction of fluorescent probes revealed that homologous pairing, the initial formation of homologously aligned joint molecules is much slower when catalyzed by human Rad51 protein than by RecA protein. Strand exchange itself, as detected specifically by the separation of contiguous fluorescent probes, is also very slow in the case of HsRad51 (23,38), as are the overall reactions promoted by ScRad51 (20), HsRad51 (22), Xrad51 (21), and HsDmc1 (this paper, see above).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In previous studies, observations on the interaction of fluorescent probes revealed that homologous pairing, the initial formation of homologously aligned joint molecules is much slower when catalyzed by human Rad51 protein than by RecA protein. Strand exchange itself, as detected specifically by the separation of contiguous fluorescent probes, is also very slow in the case of HsRad51 (23,38), as are the overall reactions promoted by ScRad51 (20), HsRad51 (22), Xrad51 (21), and HsDmc1 (this paper, see above).…”
Section: Discussionmentioning
confidence: 83%
“…Strand exchange activities have been reported for Rad51 from S. cerevisiae, Xenopus laevis, and Homo sapiens (20)(21)(22)(23), but none has been reported for Dmc1. Other studies show that both Rad51 and Dmc1 associate with synaptonemal complexes in the mouse; but according to the location and time of appearance of the two proteins during meiosis, Rad51 and Dmc1 appear to play different roles (24,25).…”
mentioning
confidence: 99%
“…In bacteria, RecA is the recombinase that catalyzes homologous pairing (Shibata et al, 1979;McEntee et al, 1979). In eukaryotes, two recombinases, RAD51 (denoted as Rad51 in Saccharomyces cerevisiae) and DMC1 (denoted as Dmc1 in S. cerevisiae), which are homologues of RecA (Aboussekhra et al, 1992;Basile et al, 1992;Bishop et al, 1992;Shinohara et al, 1992Shinohara et al, , 1993Habu et al, 1996), catalyze homologous pairing (Sung, 1994;Baumann et al, 1996;Maeshima et al, 1996;Gupta et al, 1997;Li et al, 1997;Hong et al, 2001). The mammalian and yeast genomes contain one copy each of the RAD51 and DMC1 genes (Bishop et al, 1992;Shinohara et al, 1992Shinohara et al, , 1993Habu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, the eukaryotic homologs differ from RecA in several notable respects. None of the eukaryotic enzymes appears to manifest the kinetic barrier to binding to duplex DNA (15), which in the case of RecA favors the loading of protein on single-stranded DNA; all hydrolyze ATP at a rate that is at least an order of magnitude lower than hydrolysis by RecA, and all promote recombination reactions much more slowly than RecA (10,11,12,14). Observations on human Rad51 showed that both phases of the recombination reaction, homologous pairing and strand exchange, are markedly slower than the corresponding phases of the RecA reactions (13).…”
mentioning
confidence: 99%